A history of intellectual capital measurements: from production to consumption. Issue 3 (11th July 2016) - Giuliani, Marco; Chiucchi, Maria Serena; Marasca, Stefano
Abstract : Purpose: – This paper has the ambition to enrich the extant research about the interplay between measuring intellectual capital (IC) and managing IC or, more precisely, about the production and consumption of IC measurements in practice. Stemming from these considerations, the purpose of this paper is to disentangle the production and consumption processes of IC measurements in practice. Design/methodology/approach: – This study is based on a longitudinal case study is analysed adopting an interventionist approach. Findings: – This study shows the peculiarities regarding the production and consumption of IC measurements, from several perspectives. In particular, it emerges that the reporting of IC can, in some specific contexts, lead to the non-use of IC measurements and to the disappearance of the measured object, IC. What is questionable is whether it is the loss of interest in the IC object that has led to the non-use of the IC measurements or if it is the non-consumption of the measurements and their qualities that has implied the disappearance of the measurement object. In addition, this study sheds a light on the fact that in an IC project the consumption of the measurements can occur not only at the end of the production process, but also (and may be especially) during the production process itself. This consumption can generate different effects such as the identification of new managerial objects, the establishment of new initiatives, the development of a deeper knowledge about how IC works or a change of the sense of some of the existing measurements. In all, the paper underlines the fact that how IC measurements are produced (the process followed and the "actors" involved) affects their actual consumption (or non-consumption). Research limitations/implications: – This paper contributes to the extant literature regarding the production and consumption of IC measurements. Moreover, it contributes to the field of IC "in practice" as it highlights what happens when an IC measurement system is implemented. Finally, the research work can contribute both to the studies regarding IC as an accounting change and to the ones regarding IC as a tool that facilitates organizational change. From the first perspective, the paper highlights how the introduction of IC has fostered long-lasting changes in the management accounting system, albeit circumscribed to the local (departmental) level. From the second perspective, the paper shows how IC may allow the creation of new managerial objects, thus promoting possible new actions. The main limitations of this study are related to the methodology adopted and to its specific pros and cons. Originality/value: – In comparison to previous studies, this one does not focus only on the managerial and organizational aspects related to the design and implementation of IC measurements or on their actual use, but attempts to approach them simultaneously adopting a longitudinal view. Moreover, this study does not adopt a theoretical perspective on how the indicators are designed and consumed but is aimed at investigating how these indicators are produced and consumed "in practice". Finally, this study focus on the interplay between production and consumption of indicators, i.e. on the use of IC measurements in relation to the peculiarities of their production process.